Open Practices and Resources for Collaborative Digital Pathology - Marée, Raphaël (Frontiers in Medicine, 2019)
In this paper, we describe open practices and open resources in the field of digital pathology with a specific focus on approaches that ease collaboration in research and education settings. Our Mini-Review includes open access journals and open peer review, open-source software (libraries, desktop tools, and web applications), and open access collections. We illustrate applications and discuss current limitations and perspectives.